THE USE OF ENGLISH MEMES TO IMPROVE STUDENTS’ VOCABULARY MASTERY - Eva Eliana; Darmawan Darmawan; Andi Patmasari; Mochtar Marhum (Tadulako University, 2026)
This study examined whether English memes could effectively enhance the vocabulary mastery of eighth-grade students at SMP Kristen Bala Keselamatan Palu. Vocabulary serves as the foundation of language learning because it provides learners with the lexical knowledge required to comprehend messages and communicate effectively in English. However, many students experience difficulties in mastering vocabulary because traditional teaching methods are often perceived as monotonous and less engaging. Therefore, this study proposed English memes as an innovative teaching medium to support vocabulary learning. This study adopted a quantitative research approach using a pre-experimental design based on a one-group pre-test and post-test model. The participants consisted of 30 eighth-grade students selected through cluster sampling. To measure students' vocabulary mastery, the researcher administered a 20-item vocabulary test comprising multiple-choice and word-matching questions. Data were collected through pre-test, treatment, and post-test and analyzed using descriptive statistics and a paired sample t-test with SPSS. The treatment was conducted over six meetings using English memes focusing on action verbs and descriptive adjectives. The results indicated a substantial improvement in students' vocabulary mastery. The average score rose from 45.50 on the pre-test to 88.67 on the post-test. The paired-samples t-test produced a significance value of p < 0.001, demonstrating a statistically significant difference between students' scores before and after the intervention. Based on the results, English memes can be considered an effective instructional tool for supporting vocabulary development among students.